Respuestas

2013-03-30T20:42:59+01:00

1) 3+ 4 al cuadrado- raiz de 49+ 7 * 2- 11

3 + 16 - 7 +14 -11 =

19 -7 +14 - 11=

12+ 14-11 = 

26-11= 15

 

2) raiz de 36- raiz de 121+ 4 / 2- 5 al cuadrado

 6 - 11 + 2 - 25 

-5 + 2- 25= 

-3-25= -27 

 

3) 8-(-(-2))

8 -2 = 6 ( menos por menos es mas por menos que qeda es menos) 

 

4) -(5+ raiz de 9)-(-(-4)

-5 -3 -4 =

-8 -4 = -12

2013-03-30T20:51:00+01:00

1) 3+ 4 al cuadrado- raiz de 49+ 7 * 2- 11

3 + 16 - 7 +14 -11 =0

19 -7 +14 - 11=0

12+ 14-11 = 0

R=15

 

2) raiz de 36- raiz de 121+ 4 / 2- 5 al cuadrado

 6 - 11 + 2 - 25 

-5 + 2- 25= 0

-3-25= 0

R=28

 

3) 8-(-(-2))

8 -2 = 0

R=-6

 

4) -(5+ raiz de 9)-(-(-4)

-5 -3 -4 =0

-8 -4 = 0

R=-12

ESPERO AYUDARTE